Expeditious prediction of post-mortem changes in frozen fish meat using three-dimensional fluorescence fingerprints. Issue 5 (4th May 2019) - Rahman, Md Mizanur; Shibata, Mario; ElMasry, Gamal; Nakazawa, Naho; Nakauchi, Shigeki; Hagiwara, Tomoaki; Osako, Kazufumi; Okazaki, Emiko
ABSTRACT: The present study was conducted to characterize fluorophores in the fish body using three-dimensional fluorescence fingerprints (3D-FFs) and to utilize these 3D-FFs obtained from frozen horse mackerel (Trachurus japonicus) fillets to predict early post-mortem changes. Alive fish were sacrificed instantly, preserved in ice until 2 days, and then filleted, vacuum packed, and frozen. Subsequently, 3D-FFs of the frozen fillets were acquired using F-7000 aided with a fiber probe. Post-mortem freshness changes were tracked by measuring adenylate energy charge (AEC) values and nicotinamide adenine dinucleotide (NAD and NADH) content. Partial least squares regression models for predicting AEC values and NADH content in frozen fish meat showed good fittings, with R 2 of 0.90 and 0.85, by utilizing eight and five excitation wavelengths, respectively, based on their fluorescence features acquired from standard fluorophores. This novel approach of 3D-FFs could be utilized as an efficient technique for at-line monitoring of frozen fish quality. Graphical abstract: : 3D-FFs approach for predicting the post-mortem changes in frozen fish fillets nondestructively.